Leadership Networks as a Tool of Coercion in World Politics - A. I. Podberezkin; O. A. Podberezkina (Vestnik MGIMO-Universiteta)
Social media analysis is widely used in economics, sociology, in medical studies of spreading infectious diseases and in forensic science to stop terrorist networks and drug proliferation. Social media analysis is also used in political sphere. Opinion leaders are increasingly participating in social media. The Internet is a reflection of the real world, it has the same laws as in real society. The ruling elite controls the media and social media as well as it controls the means of production. The article addresses the role of social networks in the foreign and military policies of states and other actors. The spread of leadership networks is at its early state. The potential of this Internet resource format is enormous. There is every reason to assume that economic crisis makes such resources even more popular. During economic crisis many people are left alone with their problems by their government and they are even more motivated to social cooperation and mutual assistance in social networks to receive valuable information, attention and support from the outside.